Bicycle and urban design. A lesson from Covid-19 - Fenu, Nicolò (TeMA - Journal of Land Use, Mobility and Environment, 2021)
The central role of the car in city mobility has led to a decreased capacity for people to choose another alternative form of mobility. In recent decades, some cities have set policies where cycling has become increasingly important. Urban mobility policies in response to Covid-19 have reinforced this perspective. Throughout the analysis of urban bicycle studies, the paper investigates the role of mobility for society and the design of our cities? What the role of sustainable mobility, in particular how the bicycle is addressing the Covid-19 emergency. During and after this emergency, the use of the bicycle addresses urban quality and liveability for spaces. The research studies the urban policies of 5 cities: Barcelona, Bogota, Brussels, Milan and Paris and analyses the measures implemented during the first lock down, since February 2020 to May 2020. In all cities studied, the bicycle modal shares and the bicycle infrastructure has increased. Covid-19 allowed the bicycle to prove it is the safest, most efficient urban mode of transport. The action carried out, in the cities studied, affected not only on the hard aspects reshaping the cities with permanent and temporary solutions but also on soft aspects acting on people's perception and use and choosing how to move. Transport studies and policies involving bicycles are not just ‘about cycling’, but about sustainable, productive, and prosperous cities.